(untitled) (Journal of Bangladesh Academy of Sciences, 2011)
The Tejgaon industrial area is located within the Dhaka City Corporation and is about 5 km north of the city centre. Heavy metal concentration at different sampling points varied in different seasons and the maximum amount was observed in the dry season (January). Total Fe, Pb, Cd, Mn, Ni, Zn, Cu and Cr concentrations in water samples during dry season ranged from 0.11 - 2.78, 0.733 - 2.171, 0.05 - 0.1, 0.019 - 0.34, 0.02 - 0.17, 0.01 - 0.348, 0.10 - 0.846, and 0.02 - 0.09 mg/l respectively. The present study revealed that the pollution level was very much alarming and increasing slowly day by day. According to WHO guidelines, during both wet and dry seasons 100% water samples were found in the group of "in excess of tolerable level" for Pb (0.01 mg/l). 63, 42, 79, 58 and 95% water samples were found in the group of ’in excess of tolerable level’ during dry season for Cu, Ni, Cd, Cr and Mn. Only 26% of the plant samples had Ni (< 20 mg/kg) in the normal range and 74% (? 20 - 30 mg/kg) plant samples were found in the group of "in excess of tolerable level" during dry season which was 63% (? 20 - 30 mg/kg) during wet season. Cadmium and Pb in plant samples found in the group of "in excess of tolerable level" was 26, 79% (> 10 mg kg), and 33, 59% (> 20 mg/kg) during wet and dry season, respectively. Plant samples accumulated more and tolerated higher amounts of Cr during dry season. Average concentration of Fe, Mn and Zn at different locations and plant species were 220.81, 279.33 and 239.81 mg/kg and 212.0, 313.43 and 159.19 mg/kg during wet and dry seasons, respectively. Kalmi, water hyacinth, grass (in wet season) and Boro rice, Cabbage (in dry season) accumulated the maximum concentration of Fe and Mn. In the rainy season the pollution was lower because of heavy rainfall and flushed out through the canal into the adjoining vast flood zone. DOI: http://dx.doi.org/10.3329/jbas.v35i1.7968 Journal of Bangladesh Academy of Sciences, Vol.35, No.1, 19-41, 2011